Developing Processes and Mechanisms for Managing Healthy Schools to Strengthen Attitudes to Prevent the Use of Violence in the Digital Disruption Era - Pongta, Thospon; Kaewsri, Phuripat; Sirikate, Kannapongse; Leetagool, Suchart (Ratchaphruek Journal, 2026)
This research aimed to: 1) analyze problems in the administration of well-being schools; 2) develop management processes and mechanisms; 3) disseminate the developed processes and mechanisms; and 4) formulate policy recommendations for well-being school administration to strengthen attitudes toward violence prevention in the era of digital disruption. The study was conducted in four phases. First, the current administrative problems were analyzed through questionnaires and interviews with a sample of 309 administrators and teachers, and 395 students under the Chiang Rai Secondary Educational Service Area Office in the year 2024. Data were analyzed using basic statistics and content analysis. Second, management processes and mechanisms were developed through focus group discussions with 30 stakeholders. Third, the developed model was transferred through training programs for 250 students and workshops for 150 related participants. Fourth, policy recommendations were formulated through workshops with 60 stakeholders and evaluated by 20 experts. The findings are as follows: 1) Management problems were found to be at a low level overall. The item with the highest mean score indicated that schools lacked effective systems for monitoring and tracking digital media usage. 2) The development of management processes and mechanisms based on the 4M’s conceptual framework yielded positive results. 3) Post-training assessments showed statistically significant improvements (at the .01 level) across all groups compared to pre-training assessments. Training sessions for teachers and administrators, as well as joint meetings with community representatives, received high satisfaction ratings, and 4) The policy recommendations emphasized the establishment of a collaborative learning network among government agencies, the private sector, and communities for violence prevention, with evaluation results showing high levels of congruence, appropriateness, and feasibility.